PENGARUH BEBAN ORGANIK TERHADAP EFISIENSI ANAEROBIC FIXED BED REACTOR DENGAN SISTEM ALIRAN CATU UP-FLOW - Padmono, Djoko (Jurnal Teknologi Lingkungan, 2003)
Anaerobic fixed bed reactor is a fermentation anaerobic reactor used microorganism attached growth system, where degradation of organic material done by microorganism that growth in support material as fixed film. This system mostly used for organic wastewater treatment now. The assessment is carried out for the Slaughterhouse wastewater treatmentwhere the support material for microorganism growth is a fabricated media. Plant is a demonstration scale by digester volume of 600 m . Wastewater is feeding to the digester by up flow system. The wastewater pumped from the bottom of the digester, flow through the support material, contact with the microorganism fixed on the media. Degradation of the organic waste process is take place along wastewater contact with the fixed film.Observation is on the performance of the reactor by the influence of organic loading to the pollution degradation of slaughterhouse wastewater called reactor efficiency. Fixed Bed Reactor performance still reached until 3 days hydraulic retention on organic loading rate about 3.05 kg COD/m hr, and efficiency 75 %.